Analisis Akad Syariah Terkait Transaksi ShopeePay Pada Aplikasi Shopee - Nur Annisa Baharsyam; Rahman Ambo Masse; A. Zulfikar Darussalam (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The main problem in this research is the large number of shopeepay users so that there are pros and cons in the community regarding the use of shopeepay in islam. Ustadz muhammad ihsan said that if you want to know the islamic view of e-wallet which has a function to save money digitally including shopeepay, then we need to see the contract that occurs between the user and the shopeepay company. The purpose of this study is to find out how the shopeepay transaction system is in the shopee market place and to find out how to analyze sharia contracts related to shopeepay transactions on the shopee application. This type of research uses descriptive qualitative research. In general, descriptive research is non-hypothetical research, which provides a clear and complete form of an occurrence of a phenomenon. Research in qualitative research seeks to understand the meaning of events by trying to interact with actors in these events. The results of the study show that the sharia contract used in shopeepay transactions on the shopee application is the wadi’ah contract. When viewed from the perspective of fiqh muamalah, when the user does a top-up, that's where the wadi’ah contract takes place. But in the contract, the wadi’ah itself is divided into two, namely wadi’ah yad amanah and wadi’ah yad dhamanah. Based on the results of the study, the contract that is closer to the implementation of shopeepay is the wadi’ah yad dhamanah contract. Keywords: Sharia Contract; ShopeePay; Shopee